NATURAL OCCURRENCE OF FUSARIUM MYCOTOXINS IN OIL CROP SEED - Mankeviciene, Audrone; Suproniene, Skaidre; Brazauskiene, Irena; Gruzdeviene, Elvyra (Plant Breeding and Seed Science, 2011)
Oilseeds are a perfect medium for microfungi spread and mycotoxin production. With increasing demand for oil crop produce such research has gained a special relevance since research evidence on this issue is scarce. During 2007-2009, prevalent fungi genera, including Fusarium genus, potential producer of deoxynivalenol (DON), zearalenone (ZEA), T-2 toxin (T-2) etc. were determined in our tests. The ELISA immunoenzymatic method and Veratox Fast kits were used to identify and quantify mycotoxins, while Fusarium fungi species were identified using conventional fungi determination techniques. Higher Fusarium fungi contamination level was found on linseed compared with that on spring or winter rapeseed. The difference was even more obvious in different experimental years, however, having identified Fusarium species, F. avenaceum and F. oxysporum were found to be prevalent in the seed of all crop species tested. In 2009, spring rape samples were found to contain F. dimerum which is a significant human pathogen. The presence of DON was identified in 18.2-100%, ZEA in 40 -100%, and T-2 toxin in 100% of seed samples of all oil crop species tested. From the food safety viewpoint, the concentrations determined did not exceed the levels hazardous for health, laid out in the EU regulations, however, the effect of low toxin concentrations is slow and the negative consequences manifest themselves only after some time and in various forms, which poses a serious health risk for humans and animals.